(untitled) (Research, Society and Development, 2023)
Objective: to perform the epidemiological delineation about non-melanoma skin carcinomas, regarding the evaluation of the most affected gender, age group, race, classification, anatomical site and main reconstructions performed. Method: Descriptive study on the epidemiological profile of patients with non-melanoma skin neoplasms, between the years 2019 and 2021, in the surgical center of the Polyclinic Institute of Pato Branco - PR. Data collection occurred through the analysis of medical records. Data were submitted to statistical analysis using STATA MP 14.1 software (StataCorp, College Station, TX, USA). Results: We analyzed 390 patients, 54.8% were male and 94.6% had white skin. Regarding the anatomical site, most cases were located on the face (37.7%), followed by the nose (20.8%) and upper limbs (10.1%). There was a predominance of BCC, corresponding to 70% of the cases, followed by SCC, with 28%. Regarding the type of reconstruction, primary suture was the predominant procedure with 46.2%, followed by flap-type reconstruction with 44.2%. Conclusions: The highest prevalence rates were among white men, with a mean age over 65 years, with lesions predominantly in the head and neck, and flap as the main reconstruction mechanism. Despite the low mortality of non-melanoma skin neoplasms, it has high morbidity. Thus, it is important that prevention measures, directly related to risk factors already known, as well as their control, are priority actions in the context of health care in Brazil.